Multi-source feedback following simulated resuscitation scenarios: A qualitative study - Chaplin, Timothy; Braund, Heather; Szulewski, Adam; Dalgarno, Nancy; Egan, Rylan; Thoma, Brent (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Background: The direct observation and assessment of learners’ resuscitation skills by an attending physician is challenging due to the unpredictable and time-sensitive nature of these events. Multisource feedback (MSF) may address this challenge and improve the quality of assessments provided to learners. We aimed to describe the similarities and differences in the assessment rationale of attending physicians, registered nurses, and resident peers in the context of a simulation-based resuscitation curriculum.Methods: We conducted a qualitative content analysis of narrative MSF of medical residents in their first postgraduate year of training who were participating in a simulation-based resuscitation course at two Canadian institutions. Assessments included an entrustment score and narrative comments from attending physicians, registered nurses, and resident peers in addition to self-assessment. Narrative comments were transcribed and analyzed thematically using a constant comparative method.Results: All 87 residents (100%) participating in the 2017-2018 course provided consent. A total of 223 assessments were included in our analysis. Four themes emerged from the narrative data: 1) Communication, 2) Leadership, 3) Demeanor, and 4) Medical Expert. Relative to other assessor groups, feedback from nurses focused on patient-centred care and communication while attending physicians focused on the medical expert theme. Peer feedback was the most positive. Self-assessments included comments within each of the four themes.Conclusions: In the context of a simulation-based resuscitation curriculum, MSF provided learners with different perspectives in their narrative assessment rationale and may offer a more holistic assessment of resuscitation skills within a competency-based medical education (CBME) program of assessment.